Tinjauan Hukum Islam Mengenai Kriteria Memilih Calon Pasangan Hidup (Studi Kasus pada Mahasiswa Prodi Hukum Keluarga Islam STAI Jam’iyah Mahmudiyah Tanjung Pura - Alifiyah Amanda (Journal Smart Law, 2024)
Choosing a life partner is the first stage that must be passed before marriage. Lessons about marriage including choosing a life partner have been taught especially to students of the Islamic Family Law Study Program. This study aims to determine the views of students of the Islamic Family Law Study Program at STAI Jam'iyah Mahmudiyah Tanjung Pura regarding the criteria for choosing a prospective life partner and then reviewed according to Islamic law. The research method used in this study is a qualitative research method that is descriptive in nature with an empirical approach. The informants in this study were final year students of Islamic Family Law Study Program, Head of STAI Jam’iyah Mahmudiyah Tanjung Pura and Head of Islamic Family Law Study Program. Data collection used observation, interviews and documentation methods. Data analysis by means of data reduction, triangulation and drawing conclusions. The results of the study explain the factors that are considered in choosing a life partner for students of the Islamic Family Law Study Program, STAI Jam'iyah Mahmudiyah Tanjung Pura, including religious and piety factors, economic factors and family background factors, equivalence (kufu'), physical appearance, physical and mental health, parental and family blessings with the most important factor being religious factors. The criteria for choosing a prospective life partner according to students of the Islamic Family Law Study Program, STAI Jam'iyah Mahmudiyah Tanjung Pura are divided into two, for female students the criteria are men of the same religion, men who are strong in their religion, men who are ready to lead a household, men who are able to finance their lives, diligent in working, have a gentle and loving attitude, are patient, fair and wise, honest and trustworthy and are willing to learn and improve themselves to be better. For male students the criteria are: pious women, beautiful, fertile women, virgins (not widows), knowledgeable and able to educate children and those who are not close relatives. The views of students of Islamic Family Law Study Program of STAI Jam’iyah Mahmudiyah Tanjung Pura regarding the criteria for choosing a prospective life partner are that the majority of students have demonstrated a comprehensive understanding and are in accordance with Islamic law.